Biofuel from Pyrolysis Waste Lube Oil of Refinery Unit III Using Fly Ash of Coal Combustion as a Catalyst - Nedia Sandika; Yohandri Bow; Abu Hasan (IJFAC (Indonesian Journal of Fundamental and Applied Chemistry), 2021)
Lube oil waste obtained from Utilitis Unit, Crude Distillation Unit, Crude Distillation & Ligh End Unit at Refinery Unit III Plaju Palembang South Sumatra. The process of pyrolysis of lube oil waste using fly ash catalyst is expected to produce fuel oil. Lube oil waste pyrolysis uses Fly Ash catalysts with a total catalyst of 500 gr with a temperature range variation of 0-85oC, 85-16 oC, 165-250oC, 250-300oC, and 300-350oC, while pyrolysis of waste lube oil without catalysts with a variation in the temperature range of 0-85oC, 85-165oC, 165-250oC, 250-300 oC, and 300-350 oC. Temperature range variations are referenced based on boiling route solvent fraction (0-85 oC), premium fraction (85-165 oC), kerosene fraction (165-250 oC) and diesel (250-350 oC). Solvent fraction can not be analyzed because there is no product result whether it is pyrolysis process using catalyst or without catalyst, Premium Fraction is only produced using catalyst, Sulfur content analysis result, Mercaptane sulfur, Density meets Premium fuel specification except Octane Number 76.6. Sulfur content, Density and flash point analysis of pyrolysis products using catalysts and without catalysts in accordance with kerosene products in the market. Solar fraction of pyrolysis process using catalyst and without catalyst, Analysis results density, sulfur content, Total acid number, Water Content entered solar product specifications but cetane numbers 43.2 and 45.6 have not met the specifications of solar products.